Clustering of multiallele DNA markers near the Huntington's disease gene. - MacDonald, M E (1989)
Five highly informative multiallele restriction fragment length polymorphisms (RFLPs) of value for preclinical diagnosis of Huntington's disease (HD) have been genetically characterized. One RFLP was uncovered by expansion of the D4S43 locus while three others are at D4S111 and D4S115, loci defined by NotI-linking clones. The final marker, D4S125, represents a recently discovered VNTR locus. All four loci map closer to the HD gene and to the telomere than D4S10, the original linked marker for HD. In combination with two multiallele RFLPs previously identified for D4S43 and another linked locus, D4S95, these five new multiallele markers will dramatically improve the speed and accuracy of predictive testing in HD, and increase its applicability by maximizing the chances of an informative test for anyone with appropriate family structure.